Scoping review of mobile phone app uptake and engagement to inform digital contact tracing tools for COVID-19 - Thorneloe, Rachael; Fynn, Wendy; Daly, Michael; Stanulewicz, Natalia; Kassianos, Angelos P.; Shorter, Gillian W; Moll, Sarah-Jane; Campbell, Miglena; Sodergren, Sam; Chapman, Sarah; Sutherland, Lisa; Armitage, Christopher J.; et al. (My University, 2020)
While researchers work to develop an effective COVID-19 vaccination, government and healthcare agencies across the world are developing and testing new ‘digital contact tracing’ technologies to help support the transition from emergency lockdown measures. During this transition phase, it is proposed that people will be able to move more freely, whilst ensuring continual monitoring and rapid action to tackle any new outbreaks of the COVID-19 virus.